Kinetic and Equilibrium Adsorption Studies of Methylene Blue from Aqueous Solution Using Low-Cost Adsorbent - Narayanan, Saravanan; Govindasamy, Rathika; Murugapandian Selvaraj, G.; Mohan, Priyadharsini (International Journal of Psychosocial Rehabilitation, 2019)
This study investigates the potential use of activated carbon prepared from copper pod flowers for the removal of methylene blue dye from simulated wastewater. The parameter studied included contact time, initial dye concentration, carbon dosage, temperature, and pH. The characterization of the adsorbent was carried out using Fourier transform infrared spectroscopy, scanning electron microscope, and X-ray diffraction data. The kinetic data were modeled using pseudo-first-order model, pseudo-second-order kinetic model, and intraparticle diffusion. The adsorption followed second-order rate equation. The adsorption equilibriums were analyzed with Langmuir and Freundlich isotherms. The experimental data were better interpreted by Freundlich isotherm model Langmuir isotherm model. Adsorption capacity values obtained from the Activated carbon developed from the copper pod flowers can be used as an alternative to highly efficient and low-cost abundant materials for methylene blue dye removal from wastewater.